Antibiotic prophylaxis prescribing habits in oral implant surgery in the Netherlands: a cross-sectional survey - Fabio Rodríguez Sánchez; Iciar Arteagoitia; Carlos Rodríguez Andrés; Josef Bruers (BMC, 2019)
Abstract Background There seems to be no consensus on the prescription of prophylactic antibiotics in oral implant surgery. The Dutch Association of Oral Implantology (NVOI) guidelines do not include a clear policy on prophylactic antibiotic prescriptions for oral implant surgery among healthy patients. The purpose of the study was to determine whether antibiotic prophylaxis is commonly prescribed in the Netherlands by general dentists, maxillofacial surgeons and oral implantologists in conjunction with oral implant surgery among healthy patients and to assess the type and amount of prophylactic antibiotic prescribed. Methods This observational cross-sectional study is based on a web survey. A questionnaire developed in the United States of America was translated and slightly adjusted for use in the Netherlands. It contained predominantly close-ended questions relating to demographics, qualifications, antibiotic type, prescription duration and dosage. An email including an introduction to the study and an individual link to the questionnaire was sent in February 2018 to a sample of 600 general dental practitioners and all 302 specialized dentists (oral implantologists, periodontists and maxillofacial surgeons) recognized by the NVOI. Overall, 902 questionnaires were anonymously sent. Finally, 874 potential participants were reached. Collected data were analyzed through descriptive statistics. Results In total, 218 (24.9%) participants responded to the questionnaire, including 45 females (20.8%) and 171 males (79.2%). Overall, 151 (69.9%) regularly placed oral implants. Of them, 79 (52.7%) prescribe antibiotics only in specific situations, 66 (43.7%) regularly, and 5 (3.3%) did not prescribe antibiotics at all. Overall, 83 participants who prescribe antibiotics did so both pre- and postoperatively (57.2%), 47 only preoperatively (32.4%) and 12 exclusively postoperatively (8.3%). A single dose of 2000 mg of amoxicillin orally one hour prior to surgery was the most prescribed preoperative regimen. The most frequently prescribed postoperative regimen was 500 mg of amoxicillin three times daily for five days after surgery. On average, participants prescribe a total of 7018 mg of antibiotics before, during or after oral implant surgery. Conclusions Antibiotic prophylaxis in conjunction with oral implant surgery is prescribed in the Netherlands on a large scale, and recommendations based on the last published evidence are frequently not followed.